Paper platform for determination of bumetanide in human urine samples to detect doping in sports using digital image analysis - Luiz, Vitor Hugo Marques [UNESP]; Lima, Liliane Spazzapam [UNESP]; Rossini, Eduardo Luiz [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier, 2019)
Development and application of a new, simple, inexpensive, and eco-friendly method is presented for the quantification of bumetanide in human urine samples for the detection of doping in sports. The method involves the use of a paper platform and digital image detection and is based on the reaction between bumetanide, p-dimethylaminocinnamaldehyde (p-DAC), and HCl in a methanolic medium, yielding a colored compound in a delimited area on a qualitative filter paper. The concentrations of p-DAC and HCl were optimized by a chemometric experimental design. After the addition of the reagents to the paper, digital images were obtained by scanning in a multifunctional printer and analyzed using the RGB pattern. The linear bumetanide concentration range was 6.90 × 10 −5 –1.37 × 10 −3 mol L −1 with R 2 = 0.993 and the limits of detection (LOD) and quantification (LOQ) were 3.60 × 10 −4 and 1.09 × 10 −4 mol L −1 , respectively. A SPE clean-up step for the samples were required to eliminate the interference of urinary urea. The recoveries obtained varied from 94% to 105%, indicating the absence of significant matrix effects or interferences in urine samples after clean-up step. The proposed method was successfully applied to the analysis of bumetanide in human urine samples.
Keywords: Bumetanide; Digital image analysis; Doping; Paper platform; Urine